Low-Frequency Electrical Heating for In Situ Conversion of Shale Oil: Modeling Thermal Dynamics and Decomposition - Zhaobin Zhang; Zhuoran Xie; Maryelin Josefina Briceño Montilla; Shouding Li; Xiao Li (Energies)
In situ conversion presents a viable strategy for exploiting low to moderate maturity shale oil. Traditional methods, however, require dense well patterns and substantial energy, which are major hurdles. This study introduces a novel approach employing low-frequency electrical heating via production wells to enhance heat transfer without necessitating additional heating wells. Utilizing a self-developed simulator, we developed a numerical model to evaluate the efficacy of this method in augmenting reservoir temperature and facilitating substance decomposition. Findings indicate that low-frequency electrical heating significantly elevates reservoir temperatures, accelerates hydrocarbon cracking, and boosts fluid production. A sensitivity analysis on various heating strategies and reservoir characteristics showed that elevated heating power can further pyrolyze the heavy oil in the product to light oil, while higher porosity formations favor increased oil and gas output. The study also explores the effect of thermal conductivity on heating efficiency, suggesting that while better conductivity improves heat distribution, it may increase the proportion of heavy oils in the output. Overall, this investigation offers a theoretical foundation for refining in situ conversion technologies in shale oil extraction, enhancing both energy efficiency and production quality.